P-TECH SCHOOL IN TRANSPORTATION AND SUPPLY CHAIN MANAGEMENT PROGRAM: A CASE OF BALTIMORE CITY COMMUNITY COLLEGE - Yohannes WELDEGIORGIS; Quintin DAVIS (Journal of Construction Project Management and Innovation)
Four years high school students took the opportunity of early college access and dual enrolment program by taking college courses while they are at a high school. In recent years several states including Maryland supported the development of a new model of early college access program for high school students called Pathways in Technology Early College High Schools (P-TECH) 9-14 schools. With the P-TECH 9-14 school model in six years or less students graduate with a high school diploma and a no cost two-year associate degree in STEM fields. This paper discusses the recently developed new P-TECH transportation program at Baltimore City Community College. The program focuses on the supply chain management career pathway to meet the present and future needs of the region. P-TECH schools work with industry partners and a local community college to ensure an up-to-date curriculum that is academically rigorous and economically relevant. P-TECH programs also include mentoring, workplace visits and instruction on the skills needed for the industry and paid internships and job consideration with the partnering companies.